Public opinion and the death penalty in Japan - Andreescu, Viviana (Punishment & society, 2020)
Based on the Japanese General Social Survey conducted in 2010 on a representative sample of adults, the present analysis intends to identify the factors more likely to predict variations in death penalty attitudes in Japan. Compared to death penalty proponents, those who oppose capital punishment are less likely to express punitive attitudes in general and to be dissatisfied with government expenditures on crime control. Relative to retentionists, abolitionists tend to have a higher level of social trust, show a higher level of support for public participation in the criminal justice process, are more likely to practice a religion, and are younger. Instrumental factors, such as victimization and fear of crime, symbolic factors, such as institutional trust, trust in the judiciary, and the police, as well as gender do not differentiate death penalty opponents from supporters. The results of the multinomial logistic regression show that residents who did not express agreement or disagreement with the death penalty have more in common with those who oppose capital punishment than with those who favor it. Although the majority of the population (65.2%) expressed support for death penalty, one in four respondents (26.1%) remained ambivalent regarding the use of capital punishment. Additionally, most of those who expressed an opinion (50.5%) said they would hesitate to recommend death, if chosen to serve in the newly instituted citizen judge system. Findings suggest that public support for death penalty is not as strong in the country as the Japanese government claims and that it requires further exploration.